I'm very stuck on this system problem.

Let a and b be real numbers such that a^3 + 3ab^2 = 679 and a^3 - 3ab^2 = 673. Find a - b.

Guest Jan 22, 2023

#1**+1 **

I think it is possible that you have mistyped the question but what you HAVE asked is still quite doable.

Subtract the second from the first and you get

\(6ab^2=6\\ 3ab^2=3 \)

So now I have

\(a^3+3=679\qquad and \qquad a^3-3=673\\ a^3=676\\ and\\ 3*\sqrt[3]{676}*b^2= 3\\ \sqrt[3]{676}*b^2= 1\\ b=\pm \sqrt{1-\sqrt[3]{676}}\\ a-b= \sqrt[3]{676} \pm \sqrt{1-\sqrt[3]{676}}\\\)

You need to check that, I could easily have made a careless mistake.

NOW check your question, i really do not think you wrote it down properly.

Melody Jan 23, 2023